The Potentials of Water-in-Diesel Emulsions as a Future Fuel - Nour, A. H.; Azhari, H. Nour; Said, N. (2015)
With the increasing energy prices and the drives to reduce CO2 emissions, universities and industries are challenged to find new technologies in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. The presence of water within diesel fuel in the form of water-in-diesel (W/D) emulsion reduces both particulate matter (PM) and nitrous oxide (NOx), by lowering the combustion temperature and altering the combustion pattern to more completely burn the carbon in the fuel. In this study, emulsion of W/D was prepared by high speed mixing homogenizer and the physical properties (density, viscosity, flash point, surface tension, dynamic viscosity) were investigated. Results show that the emulsions of 5%, 10%, 20% and 30% W/D were stabilized for two months, under the conditions of 2% surfactant, 3000 rpm and 15 minutes of mixing time. Under the same conditions, the stability period was limited to four weeks for emulsions with a water concentration of 40%.